2015
DOI: 10.1111/asj.12522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of active dry yeast (Saccharomyces cerevisiae) and yeast culture for growth performance, carcass traits, meat quality and blood indexes in finishing bulls

Abstract: This study was conducted to compare the effect of active dry yeasts (ADY) and yeast cultures (YC), two typical products of yeast preparations, on growth performance, carcass characteristics, meat quality and blood indexes in finishing bulls fed a high-concentrate diet. Forty-five finishing bulls (mean body weight (BW) ± standard deviation: 505 ± 29 kg BW) were allocated to three groups of 15 bulls and assigned randomly to one of three diets which were CON diet (basal diet), ADY diet (basal diet + Levucell SC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 13 publications
7
48
0
3
Order By: Relevance
“…The changes in microbial composition would further alter ruminal VFA production and constitution, which is the reason for the variations of milk fat and protein. In present study, however, no significant effect was detected on the Moisture, CP, EE and Ash content of the longissimus dorsi muscle, which was consistent with the study of Geng et al [18], though the rumen microbial population was also affected by ADY supplementation.…”
Section: Discussionsupporting
confidence: 93%
“…The changes in microbial composition would further alter ruminal VFA production and constitution, which is the reason for the variations of milk fat and protein. In present study, however, no significant effect was detected on the Moisture, CP, EE and Ash content of the longissimus dorsi muscle, which was consistent with the study of Geng et al [18], though the rumen microbial population was also affected by ADY supplementation.…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to the LD muscle CF content in this study. Previous studies (Geng et al, ) found that YC improved the intramuscular fat content (9.75 vs. 6.81, p = 0.24) compared with the control group by altering the intensity of fat metabolism, which may explain the variance of CF in this study. However, it remains unclear by what specific mechanism YC supplementation to modify lipid metabolism in animals.…”
Section: Discussionmentioning
confidence: 42%
“…These results were consistent with the current study and might be related to the increases in CP digestibility after YC supplementation (Malekkhahi et al, ). However, some findings reported that YC supplementation had no significant effect on CW or DP (Geng et al, ; Tripathi & Karim, ). These results may be ascribed to the differences in dietary compositions and YC supplementation doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory indexes included the indexes of tenderness, juiciness, and flavor. Briefly, measurement of pH, muscle color, drip loss, cooking loss percentage, and shear force refer to method of Geng, Ren, Zhou, Chang, and Meng (2016). The determination for water content, protein, intramuscular fat, and ash contents used standard procedures (AOAC, 2000), and the fatty acid was determined by capillary gas chromatography according to the method of O'Fallon, Busboom, Nelson, and Gaskins (2007).…”
Section: Methodsmentioning
confidence: 99%